Perlindungan Hukum Anak Korban International Child Abduction: Tinjauan terhadap Aspek Hukum dan Perlindungan Hak Anak - Wilda Malika Mufrihah; Elan Jaelani (Lembaga Pengembangan Kinerja Dosen, 2024)
This article aims to explore the legal framework relating to the protection of child victims of international abduction, as well as highlighting efforts that can be made to ensure security, welfare and fair solutions for the children involved. This study uses normative juridical legal research methods, namely This was done by examining statutory regulations and international conventions in the field of legal protection for child victims of international child abduction. The method used is library research or literature study. This research uses book sources and other data. This research was also carried out by reviewing and analyzing various kinds of literature. The 1980 Hague Convention on the Civil Aspects of International Child Abduction is a multilateral agreement that aims to protect children from the detrimental effects of international kidnapping by encouraging the immediate return of children who have been wrongfully appointed or detained outside their home country. The 1980 Hague Convention on the Civil Aspects of International Child Abduction is the only international legal instrument specifically designed to deal with cases of transnational child abduction. Legal protection for children in mixed marriages experiencing divorce involves various aspects that require special attention. Law Number 23 of 2002 concerning Child Protection, in Article 1 of the 1980 Hague Convention concerning Civil Aspects of International Child Abduction is a multilateral agreement that aims to protect children from the detrimental effects of international kidnapping by encouraging the immediate return of children who have been wrongfully appointed or detained outside their home country. Legal protection for children in mixed marriages experiencing divorce involves various aspects that require special attention. Law Number 23 of 2002 concerning Child Protection, in Article 1 provides a definition, what is meant by child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with their dignity and human dignity, and receive protection from violence and discrimination.